Species, fractions, and characterization of phosphorus in sewage sludge: A critical review from the perspective of recovery - Yu, Bohan; Luo, Jinghuan; Xie, Huanhuan; Yang, Huan; Chen, Shanping; Liu, Jianyong; Zhang, Ruina; Li, Yu-You (The Science of the total environment, 2021)
Phosphorus recovery from municipal sewage sludge is a promising way to alleviate the shortage of phosphorus resources. However, the recovery efficiency and cost depend greatly on phosphorus species and fractions in different sewage sludges, i.e., waste activated sludge and chemically enhanced primary sludge. In this review, the phosphorous (sub-)species and fractions in waste activated sludge and chemically enhanced primary sludge are systematically overviewed and compared. The factors affecting phosphorus fractions, including wastewater treatment process, as well as sludge treatment methods and conditions are summarized and discussed; it is found that phosphorus removal method and sludge treatment process are the dominant factors. The characterization methods of phosphorus species and fractions in sewage sludge are reviewed; non-destructive extraction of poly-P and microscopic IP characterization need more attention. Anaerobic fermentation is the preferable solution to achieve advanced phosphorus release both from waste activated sludge and chemically enhanced primary sludge, because it can make phosphorus species and fractions more suitable for recovery. A post low strength acid extraction after anaerobic fermentation is recommended to facilitate phosphorous release and improve the total recovery rate. [Display omitted] •P species & fractions in sewage sludges are compared and figured out quantitively.•P species & fractions mainly depend on P removal and sludge treatment process.•Quantitative characterization of Fe/Al–P is requisite for advanced P recovery.•Anaerobic fermentation + low strength acid is recommended for advanced P recovery.